The Right to Privacy Based on the Law of the Republic of Indonesia Number 27 of 2022 - Evelyn Angelita Pinondang Manurung (Journal of Digital Law and Policy, 2023)
The impact of technological advances and digital activities in society today affects a person's right to privacy. Potential threats and violations of a person's privacy rights containing important personal information are increasingly prevalent. Almost unrestricted digital access activities pose a threat of violating one's right to privacy. Personal data containing important information may be accessed by the Data Controller and potentially disseminated freely and irresponsibly. The right to privacy is part of the human right to obtain protection for oneself based on Article 28 Letter G section (1) The 1945 Constitution of The Republic of Indonesia. The purpose of this study is to analyze the protection of the right to privacy of personal data. This research uses normative juridical research methods by exploring legal sources. With the passing of Law Number 27 of 2022, it is hoped that it will increase understanding of the right to privacy of personal data of every citizen to be able to maintain and be responsible for the right to privacy of personal data and become a legal umbrella for the Indonesian nation in upholding justice and providing legal protection in accordance with applicable regulations.